Marine Environmental Pollution And Its Impacts On The Fulfillment Of Indigenous Peoples' Right To A Healthy Environment - Lucia Tahamata; Hattu, Vonda V. (Institute of Education and Social Research, 2024)
This research aims to analyze and understand marine environmental pollution and its impact on the fulfillment of indigenous peoples' right to a healthy environment. The study employs an empirical juridical research type, utilizing literature review based on theory, doctrine, and legal norms related to the discussed issues. This research is prescriptive, analytical, and explanatory, addressing problems based on legal provisions, norms, and theories, then analyzing them qualitatively. Ultimately, it will draw conclusions to answer the discussed problems.